The Role of Strategic Human Resource Management to Improve the Sustainable Fashion Industry in the Start-Up Perspective of Fashion MSMEs - Satria Avianda Nurcahyo; Noor Laila Ramadhani; Setya Indah Isnawati (Universitas Negeri Semarang, 2024)
This study explores the role of Strategic Human Resource Management (SHRM) in advancing sustainability within the fashion industry, particularly for Micro, Small, and Medium Enterprises (MSMEs). As sustainability awareness grows among consumers and businesses, MSME fashion startups face unique challenges due to limited resources. Using a quantitative approach with SEM PLS tools, the study collected data through questionnaires from fashion MSMEs and analyzed the relationship between SHRM and sustainable practices. The findings show that SHRM practices, such as recruiting employees with sustainability awareness, providing relevant training, enhancing communication on sustainability goals, and offering incentives aligned with sustainability, positively impact sustainability outcomes. Hypothesis testing confirmed that SHRM has a significant effect, with a t-statistic of 58.166 and a p-value of 0.000, indicating a strong, positive influence on sustainability in the fashion sector. The study highlights the importance of a strategic HR approach in supporting MSME sustainability goals, benefiting social, economic, and environmental aspects. It concludes that integrating SHRM into MSME fashion startups can enhance their competitiveness and contribute positively to the industry’s sustainable growth. This research provides key insights for MSME leaders to implement HR strategies that strengthen both business and sustainability objectives.